Jurisdiction for cross-border intellectual property infringement cases in Europe - Torremans, Paul (Kluwer Law International, 2016)
Cross-border infringement of intellectual property rights raises a number of issues. The Internet means that such cases arise ever more frequently. It is against this backdrop that this contribution looks at how the territorial international intellectual property system copes, and how EU rules on private international law can assist in resolving these issues. The contribution looks merely at jurisdiction issues, but includes suggestions to improve the private international law rules in this area.